Nanostructured Lipid Carrier: Optimization, In-vitro, In-vivo Evaluation of Nanocarrier Gel - Khare, Pragati; Rai, Janki Prasad (Journal of Neonatal Surgery, 2025)
Pharmaceutical gels are semisolid dosage form designed for application on to the skin mucus membrane and wounds. They are versatile patient friendly formulations that can deliver drugs systemically and locally. Nanostructured lipid carriers loaded gel was prepared for making the topical delivery more effective. Optimized formulation of nanostructured lipid carriers loaded gel exhibits higher in-vitro controlled release pattern as compared to marketed formulation and nanocarrier suspension. In vivo pharmacodynamic studies shows good results of wound contraction studies. These findings suggest that nanostructured lipid carriers loaded gel can serve as a promising drug delivery system to overcome the limitations of conventional formulations and provides better therapeutic outcomes